Association Between the Circulating Level of 25-Hydroxyvitamin D and Clinical Results After Cardiac Surgery: A Meta-Analysis and Systematic Review - Zhang, Yulin; Li, Jiawen; Qiu, Yu; Gong, Xue; He, Yunru; Yue, Peng; Zheng, Xiaolan; Liu, Lei; Liao, Hongyu; Zhou, Kaiyu; Hua, Yimin; Li, Yifei (Frontiers in Cardiovascular Medicine, 2021)
Background Vitamin D (VitD) is an important pleiotropic hormone for organ systems. Studies have focused on the level of VitD, especially that of 25-hydroxyvitamin D (25-(OH)-VitD), in patients after cardiac surgery and the relationship between VitD deficiency and adverse outcomes, but the results have been inconsistent. We carried out a meta-analysis to evaluate differences in the 25-(OH)-VitD level before and after cardiac surgery, and evaluated the predictive value of 25-(OH)-VitD level in the clinical outcomes of patients undergoing cardiac surgery. Methods Studies related to VitD level and cardiac surgery were searched from PubMed, EMBASE, Web of Science, and Cochrane Central Register of Controlled Trials databases from inception to October 2020. We applied the Newcastle–Ottawa Scale to assess the risk of a bias in individual studies. We examined the heterogeneity and publication bias and performed subgroup analyses and sensitivity analyses. Results Fifteen studies were included in our analysis. The 25-(OH)-VitD level was significantly lower immediately after surgery (stand mean difference (SMD), 0.69; 95%CI (0.1, 1.28), P = 0.023) and 24-h after surgery (0.84; (0.47, 1.21), 0.000) compared with that before surgery. A higher prevalence of 25-(OH)-VitD deficiency was recorded 24 h after surgery (RR, 0.59; 95%CI (0.47, 0.73), P = 0.00). Pooled results demonstrated a significant relationship between the preoperative 25-(OH)-VitD level and vasoactive-inotropic score (VIS) (SMD, −3.71; 95%CI (−6.32, −1.10); P = 0.005), and patients with 25-(OH)-VitD deficiency revealed a comparatively poor prognosis and severe condition after cardiac surgery (−0.80; (−1.41, −0.19), 0.01). However, 25-(OH)-VitD deficiency was not associated with the duration of stay in the intensive care unit. Conclusions Cardiac surgery would leads to deficiency of 25-(OH)-VitD. And the preoperative and postoperative levels of 25-(OH)-VitD are associated with adverse events, which is eligible to work as an indicator to demonstrate clinical outcomes.